Living history - Clinton, Hillary Rodham (New York, NY : Simon & Schuster, 2003)
[The author writes] about her upbringing in suburban, middle-class America in the 1950s and her transformation from Goldwater Girl to student activist to controversial First Lady. [This book] is her revealing memoir of life through the White House years. It is also her chronicle of living history with Bill Clinton. -Dust jacket.
American story -- University of life -- Class of '69 -- Yale -- Bill Clinton -- Arkansas traveler -- Little Rock -- Campaign odyssey -- Inauguration -- East wing, west wing -- Health care -- End of something -- Vince Foster -- Delivery room -- Whitewater -- Independent counsel -- D-Day -- Midterm break -- Conversations with Eleanor -- Silence is not spoken here -- Oklahoma City -- Women's rights are human rights -- Shutdown -- Time to speak -- War zones -- Prague summer -- Kitchen table -- Second term -- Into Africa -- Vital voices -- Third way -- Soldiering on -- Imagine the future -- August 1998 -- Impeachment -- Waiting for grace -- Dare to compete -- New York.
Includes index.
Accelerated Reader AR
Keywords: Clinton, Hillary Rodham; United States. -- Congress. -- Senate -- Biography; Presidents' spouses -- United States -- Biography; Legislators -- United States -- Biography; United States -- Politics and government -- 1993-2001.